2016
DOI: 10.1007/s00425-016-2619-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of symplasmic domains in the embryo and seed of Sedum acre L. (Crassulaceae)

Abstract: Main conclusion Our study demonstrated that symplasmic communication between Sedum acre seed compartments and the embryo proper is not uniform. The presence of plasmodesmata (PD) constitutes the structural basis for information exchange between cells, and symplasmic communication is involved in the regulation of cell differentiation and plant development. Most recent studies concerning an analysis of symplasmic communication between seed compartments and the embryo have been predominantly performed on Arabidop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 48 publications
1
18
0
2
Order By: Relevance
“…PD between suspensor and endosperm are found only in a few species (mainly among Sedum genus; e.g., [26]) assuming that symplasmic exchanges may occur but substantially stop early in seed development. On the contrary, our findings confirm the previously evidenced in Sedum [26,30] symplasmic connections of the suspensor cells both with the endosperm and the embryo proper cells (e.g., Figure 9A,B). Interestingly, the symplasmic communication exists till the end of embryogenesis and suspensor degradation.…”
Section: Suspensor As a Connecting Structuresupporting
confidence: 92%
See 1 more Smart Citation
“…PD between suspensor and endosperm are found only in a few species (mainly among Sedum genus; e.g., [26]) assuming that symplasmic exchanges may occur but substantially stop early in seed development. On the contrary, our findings confirm the previously evidenced in Sedum [26,30] symplasmic connections of the suspensor cells both with the endosperm and the embryo proper cells (e.g., Figure 9A,B). Interestingly, the symplasmic communication exists till the end of embryogenesis and suspensor degradation.…”
Section: Suspensor As a Connecting Structuresupporting
confidence: 92%
“…Recent studies on Sedum acre in Crassulaceae have analyzed symplasmic communication between the basal cell and the embryo proper and endosperm. These studies showed that symplasmic communication is nonuniform [30]. Indeed, despite many important studies about the embryogenesis of Crassulaceae, there is a lack of a detailed description of ultrastructural aspects for a large number of genera from this family.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments conducted on S. acre revealed that the discovered plasmodesmata are functional, but only in directions of the basal cell-embryo proper and basal cell endosperm. Movement of symplasmic transport fluorochromes in the opposite direction was not detected, so probably they are limited (Wróbel-Marek et al 2017 ). Unidirectional movement through plasmodesmata was not fully confirmed, but data revealed such a possibility (Wróbel-Marek et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Movement of symplasmic transport fluorochromes in the opposite direction was not detected, so probably they are limited (Wróbel-Marek et al 2017 ). Unidirectional movement through plasmodesmata was not fully confirmed, but data revealed such a possibility (Wróbel-Marek et al 2017 ). Possibly, during megasporogenesis, such plasmodesmata regulated the flow of the nutritional substances, but this is only a hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…The funiculus phloem reaches a phloem-unloading domain at the chalazal area of the outer integument, which either alone or together with the inner integument evolves to the seed coat, which differs between seed species as well. Using fluorescent probes, it has been shown that the entire outer integument at the end of the vascular bundle sheath of the funiculus is an extended symplasmic domain in Arabidopsis thaliana [99], and in Crassulaceae seeds [100], the inner integument and the embryo are separated symplasmic domains. In legumes,…”
Section: Symplasmic Conductivity In Seedsmentioning
confidence: 99%